Nghiên cứu sự tạo phức của một số ion kim loại với glyxin bằng phương pháp phân tích nhiệt - Huỳnh, Lê Văn (Vietnam Journal of Chemistry, 2017)
The complex has been increasingly widely used in many fields such as industry, agriculture, manufacturing, new materials, food, cosmetics, wastewater treatment for environmental protection and metabolic organic compounds. In agriculture, it has been used as micronutrient fertilizer complexes with amino acids, increase soil fertility, increase rice production and tea. Done, not complex yet can also be used in practice, because each complex is characterized by constant reliability. If the mixture has a constant strength is too large, there is no catalytic activity, if there is a constant complex durable too small, vulnerable to hydrolysis are alkaline, some complexes have catalytic activity. Therefore, only a number of new complexes have potential application in the production process technology. This paper is the research results of some of the complexing metal ions Cu2+; Zn2+ and Ni2+ with glycine by thermal analysis methods. Keywords. Research on the complex, thermal analysis method.